The Impact of Islamic Business Ethics on Multinational Corporate Practices - Haruni Ode; Faisal Razak; Nurul Huda (Sharia Oikonomia Law Journal, 2024)
It is important to understand the role and influence of Islamic business ethics on the actions of multinational corporations (MNCs) in an increasingly connected world. The question of how Islamic values and principles can influence business decisions has become a subject of great concern in the era of globalization that presents increasingly complex ethical challenges for multinational companies. This study aims to learn more about how Islamic business ethics affect the operations of multinational companies. This study not only seeks the immediate results of implementing Islamic principles in business decision-making, but also examines its long-term effects on corporate reputation, stakeholder relations, and operational sustainability. Literature analysis, case studies, and interviews with stakeholders in multinational companies implementing Islamic business ethics policies. This method allows researchers to gain a broad understanding of how these principles are applied in the daily life of the company and how various parties interact with the policy. Research shows that implementing Islamic business ethics in the practices of multinational companies can have significant effects, from increasing stakeholder trust and loyalty to improving financial performance and corporate reputation. This study finds that ethical principles are very important in business decision making, especially for multinational companies that have influence around the world. MNCs can use the integration of Islamic business ethics to gain competitive advantage and build a strong foundation for the growth and development of more just and sustainable societies around the world.